PERAN INTERAKSI SOSIAL DALAM PERKEMBANGAN EMOSIONAL ANAK SEKOLAH DASAR - Okta Nadia, Deni; Suhaili, Neviyarni; Irdamurni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is a literature study that aims to describe the role of social interaction in the emotional development of elementary school children. Emotions are an important component of a child's life and can have a significant effect on their well-being. Social interactions, including with peers, family, and teachers, have great potential in shaping the emotional development of primary school children. This research involves an analysis of various literature sources related to the topic. The results of the analysis showed that social interaction plays a crucial role in the emotional development of elementary school children. Through social interaction, elementary school children learn to recognize, express, and manage their emotions. In the context of primary school children's emotional development, social interaction can affect their social adjustment, psychological well-being, and adaptability in a variety of situations. Therefore, a deep understanding of the role of social interaction in the emotional development of primary school children is essential in designing effective educational programs. This research provides better insight into the importance of social interaction in the emotional development of primary school children. The implications of this research can be used as a foundation for the development of educational approaches that focus on developing social skills, emotional regulation, and emotional well-being of primary school children.